2017
DOI: 10.3329/dujps.v16i1.33390
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacteria with Biochemical and Pharmacological Importance from Soil Samples of Dhaka City

Abstract: Abstract:We studied soil samples from Dhaka municipality area to isolate and characterize bacteria having potential biochemical and pharmacological importance. Total twenty five soil samples were collected from fish, vegetables and fruits dump area from Dhaka City. Bacterial population was sub-cultured in trypticase soya agar (TSA) plate.Nineteen colonies were isolated, cultured and characterized by gram staining and biochemical tests. Six isolates were found to be gram negative while thirteen were gram positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
(15 reference statements)
1
13
0
1
Order By: Relevance
“…In this research, bacteria that produce extracellular enzymes (amylase, cellulase and protease) were isolated from soil samples. Begum et al [17] reported that soil bacteria have potential of being unique and exploited for commercial and industrial use. Production of protease by Bacillus, Enterobacter, Klebsiella and Staphylococcus observed in this study has been reported [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In this research, bacteria that produce extracellular enzymes (amylase, cellulase and protease) were isolated from soil samples. Begum et al [17] reported that soil bacteria have potential of being unique and exploited for commercial and industrial use. Production of protease by Bacillus, Enterobacter, Klebsiella and Staphylococcus observed in this study has been reported [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial isolate (K1) was identified on the basis of cell morphology and biochemical tests (Begum et al, 2017). Biochemical tests were performed using VITEK ® 2 system (bioMérieux, France) through colorimetric identification.…”
Section: Methodsmentioning
confidence: 99%
“…Kirby-Bauer disc diffusion method was adopted to evaluate the antibiotic sensitivity pattern of Staphylococcus aureus K1 against selected antibiotics (CLSI, 2013). Commercially available antibiotic discs (Oxoid™ UK) were used in this study including ceftriaxone (30 µg), ampicillin (10 µg), amoxicillin (30 µg), meropenem (10 µg), imipenem (10 µg), sulphamethoxazole/trimethoprim (25 µg), nalidixic acid (30 µg), cefoxitin (30 µg), ciprofloxacin (5 µg), ofloxacin (5 µg), ceftazidime (30 µg), aztreonam (30 µg), gentamycin (10 µg), vancomycin (30 µg), ertrapenem (10 µg), amikacin (30 µg), piperacillin/tazobactam (110 µg) and cefepime (30 µg) (Begum et al, 2017). The tests were conducted following manufacturer instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Then the isolated bacterias were applied and mixed slowly by using an ose needle. Then, the positive results are marked by the formation of air bubbles in the surrounding colonies (Begum et al, 2017).…”
Section: Catalase Testmentioning
confidence: 99%
“…Stubbing to the butt and streaking the slant, it was incubated at 37 o C for 24 hours. Positive reactions are characterized by the presence of black precipitate on media (Brown, 2010;Begum et al, 2017).…”
Section: H 2 S Testmentioning
confidence: 99%